The Verb "Dyšat’" in Modern Russian: Some Remarks - Thomières-Shakhovskaya, Irina (Cuadernos de Rusística Española, 2024)
This article will deal with the verb dyšat’ in modern Russian. My aim is to describe the combinability of this lexeme. For example, dyšat’ can have one or two arguments, and can also be used with different types of adverbs. If there is only one argument – the subject – it refers to the process of breathing itself. The use of adverbs makes it possible to evaluate breathing in relation to a norm (tjaželo, nerovno). In the presence of two arguments, the second argument often refers to a part of the body (grud’, rot, etc.) and is used with a preposition. In both cases, the semantic nature of the arguments will be analysed in detail. Finally, I consider the idiomatic expressions (dyšat’ pol’noj grud’ju), as well as the metaphorical uses of the verb breathe (zdes’ vsë dyšit pokoem). The article is part of a study carried out at the Centre de Linguistique en Sorbonne UR7332. The purpose is a detailed description of the lexicon of different languages. My basis is the theory of Zellig Harris (1976) and my examples and my statistics are from www.ruscorpora.ru which explains the innovative dimension of this article.